2022
DOI: 10.20546/ijcmas.2022.1106.037
|View full text |Cite
|
Sign up to set email alerts
|

Gladiolus Hybrids for Commercial Traits and their Evaluation

Abstract: The present experiments were conducted with twenty-eight gladiolus hybrids along with check at the research farm of the Division of Floriculture & Landscaping, ICAR-Indian Agricultural Research Institute, New Delhi during the year 2021-22 to study the gladiolus hybrids for commercial traits and their performance and suitability for commercialization and profitability. The mean performance of gladiolus hybrids data were highly significant for all the traits studied. The results indicated that early flowerin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
1
0
Order By: Relevance
“…Thus, this result indicated that plant height decreases with the decrease in temperature. According to Joshna et al (2015), Sharma et al (2018), and Swaroop et al (2018), the results of this study are comparable with those results. However, among the varieties, Litouween had the tallest plants (97.06 cm), while Pavia had the shortest plants (83.38 cm).…”
Section: Resultssupporting
confidence: 90%
“…Thus, this result indicated that plant height decreases with the decrease in temperature. According to Joshna et al (2015), Sharma et al (2018), and Swaroop et al (2018), the results of this study are comparable with those results. However, among the varieties, Litouween had the tallest plants (97.06 cm), while Pavia had the shortest plants (83.38 cm).…”
Section: Resultssupporting
confidence: 90%
“…Similar variations in number of leaves had been reported by Swaroop et al [8] and Susila [9] in gladiolus. [12].…”
Section: Resultsmentioning
confidence: 99%